쌀이 맑고 재배안정성이 우수한 조생종 벼 ‘새오대1호’ - 구본일(Bon-Il Ku); 전용희(Yong-Hee Jeon); 원용재(Yong-Jae Won); 안억근(Eok-Keun Ahn); 정국현(Kuk-Hyun Jung); 현웅조(Ung-Jo Hyun); 곽지은(Jie-Un Kwak); 이정희(Jeong-Heui Lee); 김정주(Jeong-Ju Kim); 박향미(Hyang-Mi Park); 이윤승(Yoon-Sung Lee); 이점호(Jeom-Ho Lee); et al. (Korean journal of breeding, 2024)
Rice cultivar ‘Saeodae1’ was generated by crossing ‘Saeodae’, which has goodtaste and a medium-short round grain, and ‘Unbong51’ which has a combined disease resistanceand translucent grain. The aim of this was to develop an early maturing rice cultivarwith medium-short round grain and high quality rice which adapts to the mid-northern inlandplain, northern-middle highland, northern-east coastal region of Korea, and was undertakenby the rice breeding team of Cheolwon Substation, National Institute of CropScience (NICS), RDA, in 2022. In the normal growing season in the mid-northern inlandplain of Korea, the heading date of ‘Saeodae1’ was July 25 around the same time in ‘Odae’. ‘Saeodae1’ had a 75 cm culm length, 1 cm longer than that of ‘Odae’, and 75 spikelets perpanicle, similar to that of ‘Odae’. The ripened grain ratio (84.7%) of ‘Saeodae1’ was higherthan that (72.5%) of ‘Odae’. The head rice ratio (60.9%) of ‘Saeodae1’ was higher than thatof ‘Odae’, which is advantageous in securing yield. 1,000 grain weight (25.9 g) was similarto that of ‘Odae’, but it has a smaller degree of white core rice, leading to an improved consumerpreference. ‘Saeodae1’ exhibited resistance to blast and bacterial blight (K1, K2, K3races), but was susceptible to the K3a race of bacterial blight, stripe virus, dwarf and blackstreak dwarf viruses, and plant-hoppers. The milled rice of this variety was translucent,with a medium-short grain shape. The cooked rice grains of ‘Saeodae1’ exhibited a goodpalatability index (0.13) and similar amylose content (18.2%) to that of ‘Odae’. Grain millingcharacteristics, including head rice milling recovery ratio and head rice ratio (82.0%) werebetter than those of ‘Odae’. Average milled rice productivity of ‘Saeodae1’ was 5.59 t/haat six sites in the normal growing season (Registration No. 10182(2024.5.14.)). KCI Citation Count: 0